“Disgrace, Distress and Death: Traumatized Women in Partition Fiction” - Gautam, Devi Prasad (Advances in Social Sciences Research Journal, 2022)
This paper analyzes fictional works written around the massive violence of Partition of South Asia into two nations--India and Pakistan--in 1947. It reads short stories such as Saadat Hasan Manto’s “The Return,” Kartar Singh Duggal’s “Kulsum,” Khadija Mastur’s “They Are Taking Me Away, Father, They Are Taking Me Away,” and Ghulam Abbas’s “Avtar: A Hindu Myth;” and novels like Khushwant Singh’s Train to Pakistan, Bapsi Sidhwa’s Cracking India, Bhisham Sahni’s Tamas, and Chaman Nahal’s Azadi to examine the impact of the genocidal violence specifically on female characters. The study finds that the fictional texts corroborate with the theoretical arguments of scholars such as Urvashi Butalia, and Ritu Menon and Kamla Bhasin that notwithstanding the suffering of millions of people, the irrational Partition made women the worst victims of the subcontinent’s tragedy highlighting the moments when they are abducted, raped, kept as mistresses, forced to work as prostitutes, traded, or even killed. The texts show that—despite rare moments of women’s agency—men from the warring communities in both nations sexually exploit vulnerable women mostly from the opposing community. The paper argues that the scenes of intense physical and psychological pain of women depicting their dishonor, disgrace, distress, trauma, or death in the examined works reveal that men assaulted vulnerable women not only to flaunt their own manliness but also to demean the religion and the manhood of the victimized community.